2008
DOI: 10.1017/s1461145708009334
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the cortical processing of novel and target stimuli by drugs affecting glutamate and GABA neurotransmission

Abstract: In this double-blind, placebo-controlled study, we examined the effects of subanesthetic doses of ketamine (an NMDA glutamate receptor antagonist) and thiopental (a GABA-A receptor agonist) on the event-related potential (ERP) correlates of deviant stimulus processing in 24 healthy adults. Participants completed three separate pharmacologic challenge sessions (ketamine, thiopental, saline) in a counterbalanced order. EEG data were recorded both before and during each challenge while participants performed a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 57 publications
10
61
0
Order By: Relevance
“…This finding is consistent with previous studies in the auditory and visual domains (47)(48)(49)(50)(51)(52)(53)86) although we observed a strong effect only in the encoding phase with the retrieval significance reduced to a trend. We also found a trend for correlation between P300 and cognitive performance under ketamine for both encoding and retrieval conditions.…”
Section: P300supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies in the auditory and visual domains (47)(48)(49)(50)(51)(52)(53)86) although we observed a strong effect only in the encoding phase with the retrieval significance reduced to a trend. We also found a trend for correlation between P300 and cognitive performance under ketamine for both encoding and retrieval conditions.…”
Section: P300supporting
confidence: 93%
“…Studies so far have focused on auditory oddball paradigms and reported reductions in P300 as well as a marker of automatic WM update, mismatch negativity (47)(48)(49)(50). Visual experiments have focused exclusively on later ERP components, reporting an attenuation of the P300 component (51)(52)(53).…”
Section: Q4mentioning
confidence: 99%
“…Reductions in P300 amplitude and increased latencies have been observed in a number of other neuropsychiatric disorders including schizophrenia (reviewed in Bramon et al, 2004;Jeon and Polich, 2003). Both GABAergic and glutamatergic systems have been strongly implicated in contributing to the P300 (Watson et al, 2009). In fact, it is now recognized that ERPs such as the P300 are generated by inhibitory and excitatory postsynaptic potentials, which are primarily driven by the release of glutamate and GABA (Luck et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the magnitude of the hemodynamic response of the fMRI-BOLD signal in the visual cortex was reduced in individuals with larger GABA levels in this region, possibly through an effect on local circulation or glutamate levels (Muthukumaraswamy et al, 2009). Pharmacological studies complement this finding by showing that GABA agonists reduce perceptual awareness (van Loon et al, 2012) and visual discrimination (Giersch & Herzog, 2004), and attenuate the neurophysiological response to visual oddball stimuli (P3 event-related brain potential component; Watson et al, 2009). Further studies showed that GABA agonists also impair temporal discrimination of auditory intervals (Rammsayer, 1992(Rammsayer, , 1999.…”
Section: Individual Differencesmentioning
confidence: 94%